Alcohol and sweet reward are encoded by distinct meta-ensembles - Wandres, Miriam; Pfarr, Simone; Molnár, Botond; Schöllkopf, Ursula; Ercsey-Ravasz, Maria; Sommer, Wolfgang H.; Körber, Christoph (Neuropharmacology, 2021)
Cue-reward associations form distinct memories that can drive appetitive behaviors and cravings for both drugs and natural rewards. It is still unclear how such memories are encoded in the brain's reward system. We trained rats to concurrently self-administer either alcohol or a sweet saccharin solution as drug or natural rewards, respectively. Memory recall due to cue exposure reactivated reward-associated functional ensembles in reward-related brain regions, marked by a neural cFos response. While the local ensembles activated by cue presentation for either reward consisted of similar numbers of neurons, using advanced statistical network theory, we found robust reward-specific co-activation patterns across brain regions. Interestingly, the resulting meta-ensemble networks differed by the most influential regions, which in case of saccharin comprised the prefrontal cortex, while for alcohol seeking control shifted to insular cortex with strong involvement of the amygdala. Our results support the view of memory representation as a differential co-activation of local neuronal ensembles. This article is part of the special issue on ‘Neurocircuitry Modulating Drug and Alcohol Abuse’.
Gesehen am 05.11.2021